Teaching Speaking by Using Talking Stick Technique - Khairunnisa Khairunnisa; Asnawi Asnawi; Yuliana Yuliana (Universitas Syiah Kuala, 2020)
The objective of this study is to figure out whether the use of Talking Stick Technique improves the second year students of SMPN 14 Banda Aceh in speaking. The population of this study was all the second grade students in this school, and the sample of this study was the VIIIA class which consisted of 30 students. The writer applied quantitative method with one group pre-test and post-test design, in which the students were given oral tests before and after the teaching treatment took place as part of data collection. The writer adopted the procedure of Talking Stick technique by Lie (2008) in teaching speaking for the students. After the treatment and the tests were accomplished, it showed that the students had made better change in their speaking ability. It was proven by the increase of the fluency aspect which some students could reach the category of very good , where no one could reach this category in post-test .Where the mean score of the pre-test was 55.93 then increased in the post-test to become 69.76. Furthermore, the statistic also showed that t-test was 13.83 and t-table 2.045. As the t-test score was higher than t-table, it indicated that the students in the experimental class who were taught by using Talking Stick Technique got better improvement in their speaking skill.